7차 전력수급계획에 따른 송전계통 손실 분석에 관한 연구 - 김성열(Sung-Yul Kim); 이여진(Yeo-Jin Lee) (전기학회 논문지 P권, 67(2), 2018)
In recent years, decentralized power have been increasing due to environmental problems, liberalization of electricity markets and technological developments. These changes have led to the evolution of power generation, transmission, and distribution into discrete sectors and the division of integrated power systems. Therefore, studies are underway to efficiently supply power and reduce losses to each sector's demand. This is a major concern for system planners and operators, as it accounts for a relatively high proportion of total power, with a transmission and distribution loss of 4-6%. Therefore, this paper analyzes the status of loss management based on the current transmission and distribution loss rate of each country and transmission loss management cases of each national power company, and proposes a loss rate prediction algorithm according to the long-term transmission system plan. The proposed algorithm predicts the demand-based long-term evolution and the loss rate of the grid to which the transmission plan is applied.